Integrating English Language Materials and Islamic Values: Research and Development in Islamic Higher Education - Wati, Ning Setio; Kuryani, Kuryani (Tapis: Jurnal Penelitian Ilmiah, 2024)
Developing English material is an effort to develop and validate English material based on students' characteristics and students’ needs. Students of Islamic universities have different characters and needs from general universities. Therefore, this study aims at describing the process of developing English language material for Islamic learners in Islamic higher education based on students’ needs. The method of this research was Borg and Gall's research and development model. In this study, the researchers employed the procedures in four steps only such as research and collecting the data, planning, and developing the product. The participants of the study were the second students semester of the Islamic education study program (PAI) of Tarbiyah Faculty of a private Islamic university in Indonesia. The number of participants involved in this model was 30 participants. The researchers collected the data by using questionnaires, and interviews. The product of this study was evaluated by two experts between English language teaching and Islamic materials. The data was analyzed in qualitative and quantitative analysis. The results of this study showed that the developing English materials based on the integration of English language materials and Islamic values for the students of Islamic higher education are developed by the researchers in appropriate quality.